Arabinose based gelators: rheological characterization of the gels and phase selective organogelation of crude-oil. Issue 95 (27th September 2016) - Rajkamal,; Pathak, Navendu Prakash; Chatterjee, Debnath; Paul, Abhijit; Yadav, Somnath
Abstract : Detailed characterizations, including rheological studies of new triazolyl arabinoside based organogelators which are effective for PSOG of crude-oil are reported. Abstract : Oil-spills, whether marine or terrestrial, result in major devastation to the environment and ecosystem, loss of habitat and damage to the economy. While inevitable in the current scenario, oil spillages necessitate prompt remedial action to limit the damage caused. A recent strategy towards this is to congeal the spilled oil into a gel through gelation (for terrestrial oil-spills) or through Phase Selective Organogelation (PSOG) for marine oil-spills which can stem the spread of the oil and also provide for the easy removal and reclamation of the gelled oil. Herein, we report two triazolylarabinoside derivatives that are stable, completely insoluble in water and can carry out the gelation as well as the PSOG of hydrocarbon based organic solvents, petrol, diesel and also crude-oil. The gels have been characterized thoroughly by optical microscopy, FESEM, AFM, XRD and rheological experiments. The gelation of crude-oil has also been unequivocally established via rheological studies. The easily synthesized and cheap triazolylarabinosides could provide simple gelators for the remediation of marine/terrestrial oil-spills.